Boganmeldelser - Kåre Bødal; Lars Adam Rehof; Ole Krarup; Sysette Vinding Kruse; H. Kallehauge; Henrik Stevnsborg; Britta Kyvsgaard; Nils Christie; Jørn Simonsen; Margaretha Järvinen; Beth Grothe Nielsen; Arne Baun; et al. (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews